Fan service ebook - Danan, Rosie (2025)
The truth is stranger than fan fiction in the next sexy paranormal rom-com from the beloved author of The Roommate . The only place small-town outcast Alex Lawson fits in is the online fan forum she built for The Arcane Files , a long-running werewolf detective show. Her dedication to archiving fictional supernatural lore made her Internet-famous, even if she harbors a secret disdain for the show’s star, Devin Ashwood. (Never meet your heroes—sometimes they turn out to be The Worst.) Ever since his show went off the air, Devin and his career have spiraled, but waking up naked in the woods outside his LA home with no memory of the night before is a new low. It must have been a coincidence that the once-in-a-century Wolf Blood Moon crested last night. The claws, fangs, and howling are a little more difficult to explain away. Desperate for answers, Devin finds Alex—the closest thing to an expert that exists. If only he could convince her to stop hating his guts long enough to help.... Once he makes her an offer she can’t refuse, these reluctant allies lower their guards trying to wrangle his inner beast. Unfortunately, getting up close and personal quickly comes back to bite them.